Academic Bibliography : Universiteit Gent.
Welcome to the Academic Bibliography and Institutional Archive of Ghent University. This database registers the scientific publications of UGent researchers, including articles, books, book chapters, conference proceedings and other material.
Keywords: Bibliografieën; E-books.; Eindwerken; Tijdschriftartikels